The nonlinear theory of the electromagnetic field excitation in orbitron - Kirichenko, Yu.V.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2009)
The nonlinear theory of electromagnetic waves generation in orbitron is developed. The set of the equations including
the equations of field excitation and the equations of 2-dimential motion is constructed and numerically solved. It
is shown, that mechanism of electron bunching and energy exchange of electrons with the wave in orbitron and in
magnetron has much in common. For the fixed parameters of orbitron from the point of view of generated energy
and electronic efficiency there is some optimal value of electron density in the interaction region. В роботi розвинуто нелiнiйну теорiю генерацiї електромагнiтних хвиль в орбiтронi. Побудовано i
чисельно розв’язано систему рiвнянь , що включає рiвняння збудження та руху. Показано, що механiзми групування та обмiну енергiєю електрона з хвилею в орбiтронi та магнетронi мають багато
спiльного. Для фiксованих параметрiв орбiтрона щiльнiсть електронiв у просторi взаємодiї має оптимальне значення з точки зору енергiї, що генерується, та коефiцiєнта корисної дiї. Достатньо точний
опис процесу збудження хвиль в орбiтронi можна отримати за допомогою основної власної гармонiки. В работе развита нелинейная теория генерации электромагнитных волн в орбитроне. Построена и
численно решена система уравнений возбуждения и уравнений движения. Показано, что механизмы
группировки и обмена энергией электрона с волной в орбитроне и магнетроне имеют много общего.
Для фиксированных параметров орбитрона имеется некоторое оптимальное с точки зрения генерируемой энергии и электронного коэффициента полезного действия значение плотности электронов в
пространстве взаимодействия. Достаточно точное описание процесса возбуждения волн в орбитроне
можно получить, ограничиваясь основной собственной гармоникой.